Analisis Pengaruh Harga Minyak Dunia, Harga Emas DanBank Indonesia Rate Terhadap Dana Pihak Ketiga PadaBank Syariah Di Indonesia Periode 2010-2014 - Andriyani, Ashari; , Siti Fatimah, SE, M.Si; , Drs. Harun M.H (2017)
This research aims to analyze the influence of the world oil price, the gold price and the Bank Indonesia rate on the third party fund in the Islamic bank in Indonesia in the period of 2010-20140. The data used in this research are secondary data in the form of monthly time series. The analysis model used in this research is multiple linear regression with the method of Error Correction Model (ECM). The results of the research revealed that the results of the normality test of the data using the model of Jarque Bera has a normal distribution. The results of the liniearity test using the model of Ramsey Reset of the regression model has a linier form. The results of the classical assumption test revealed that there is no problem of multicoliniearity, no problem of heterocedasticity and no problem of autocorrelation. From the t test, it can be known that the variables of the world oil price, the gold price and BI rate, in a short term, have no influence on the third party fund in the Islamic bank in Indonesia, meanwhile, in a long term, the variables of the world oil price and the gold price have influence on the third party fund in the bank Islamic in Indonesia. The results of f test revealed that the model which was used existed. The determination of R2 is as much as 0.301072 that means that 30.1% of the variation of score variable of the third party fund can be explained by the variables of the oil price, the gold price and BI rate, meanwhile, the rest 69.9% is explained by other independent variables excluded in the model.